Cell signaling in breast cancer associated with neurofibromatosis type 1 - Viitamäki, Sini (My University, 2020)
Neurofibromatosis 1 (NF1) is an autosomal dominant disorder caused by mutations in the NF1 gene, which codes tumor suppressor protein neurofibromin. The incidence of NF1 is approximately 1:2000. Patients with NF1 are at an increased risk of cancers such as tumors of the breast. Somatic NF1 mutations also occur in breast cancers without NF1 syndrome: approximately 30% of all breast cancers harbor NF1 gene alterations. Neurofibromin is a major negative regulator of Ras protein in the Ras signaling pathway. Most breast cancers harbor pathogenic mutations in genes involved in the Ras signaling pathway. Hence, this pathway is considered important in breast cancer pathogenesis. In this study, the effects of three Ras signaling pathway inhibitors on the phosphorylation of Extracellular signal-regulated kinase 1/2 (ERK1/2) and the viability of breast cancer cells lines were studied. Neurofibromin deficiency was modeled with siRNA-mediated knockdown of the NF1 gene expression. The aim was to determine whether NF1 deficiency affects the sensitivity of the breast cancer cell lines to LY294002, U0126 and rapamycin inhibitors. The study was carried out with breast cancer cell lines MCF7, BT-474, BT-20 and human primary skin fibroblasts. The results indicate that NF1 deficiency did not interact with the effects of inhibitor treatment in terms of viability in any of the cell lines. Furthermore, the inhibitors did not affect the phosphorylation of ERK1/2 differently between the NF1 knockdown and control cells. These results suggest that the NF1 status does not affect the sensitivity of breast cancer cells to these targeted inhibitors.
Keywords: Neurofibromatosis 1, breast cancer, Ras signaling pathway